PENGEMBANGAN DESTINASI BERKUALITAS DI BALI - Santosa, I Nengah; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 1 No 1 (2013): VOL 1, NO 1 (2013): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2013.v01.i01.p01, 2013)
ABSTRACT In the development of tourism destinations in Bali have a comprehensive development plan, in order to obtain the optimal benefits for the community, both in terms of economic, social and cultural. Type of data used in the form of qualitative data, primary and secondary data sources, data collection techniques through observation, interviews, and literature. Determination of informants by purposive sampling techniques and use descriptive-qualitative data analysis. Development of quality destinations in bali is done by stages include: improving the quality of human resources, engage and empower people, build a community-based tourism, quality tourism products packaging, packaging components tourism product, tourism service pack, recruit qualified travelers.
Keywords: Keywords: tourism destination, community based tourism, tourism product.